2014
DOI: 10.1002/bjs.9345
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing survival after D1 or D2 gastrectomy for gastric cancer

Abstract: ISRCTN11154654 (http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(160 citation statements)
references
References 23 publications
8
147
0
5
Order By: Relevance
“…An essential condition is that good early postoperative results in terms of morbidity and mortality should be ensured. This is consistent with the reports of observational non-randomized studies from specialized centers (6)(7)(8)(9)18,(26)(27)(28).…”
Section: Lymphadenectomy For Advanced Formssupporting
confidence: 92%
See 2 more Smart Citations
“…An essential condition is that good early postoperative results in terms of morbidity and mortality should be ensured. This is consistent with the reports of observational non-randomized studies from specialized centers (6)(7)(8)(9)18,(26)(27)(28).…”
Section: Lymphadenectomy For Advanced Formssupporting
confidence: 92%
“…The 15-year follow-up evaluation of the Dutch trial showed a trend to overall survival improvement in D2 group, although not statistically significant; if we could virtually exclude this initial gap, long-term survival difference may be much higher, probably statistically significant (11). In the Italian trial by Degiuli et al, better long-term outcome was observed in patients with N2 tumors treated by D2 dissection compared with D1; in such trial, postoperative mortality was overlapping in the D1 and D2 groups (27). Then, it is probable that D2 dissection, when performed in specialized, high-volume centers, could offer a longterm survival benefit if postoperative complications and mortality are not increased.…”
Section: Potential Improvement In Long-term Survivalmentioning
confidence: 81%
See 1 more Smart Citation
“…Nonrandomized Asian series have demonstrated improved os with D2 lymphadenectomy, making it the standard of care in East Asia [40][41][42][43][44][45] . However, randomized Western studies and a meta-analysis of D1 compared with D2 lymphadenectomy failed to reproduce the os benefit observed in the retrospective Eastern studies [46][47][48][49] . In 1997, the Union for International Cancer Control and the American Joint Committee on Cancer, in the 5th edition of their staging manual, recommended that a minimum of 15 lymph nodes be assessed per patient 50 .…”
Section: Summary Of Evidencementioning
confidence: 94%
“…In 2014 Degiuli et al published the results from a randomized clinical trial in which 267 patients submitted to D1 or D2 lymphadenectomy did not show a significant difference in survival (27). However, a closer look at the study reveals that numerous patients considered as D1 actually underwent a more extended lymphadenectomy, resulting in substantial uniformity between the two procedures.…”
Section: Recent Studiesmentioning
confidence: 99%